Calcium carbonate microparticle templates using a PHOS‐b‐PMAA double hydrophilic copolymer. (25th September 2013) - Mihai, Marcela; Mountrichas, Grigoris; Pispas, Stergios; Stoica, Iuliana; Aflori, Magdalena; Auf der Landwehr, Maria; Neda, Ion; Schwarz, Simona
<x xml:space="preserve">Abstract</x> The crystallization characteristics of calcium carbonate microparticles grown from supersaturated aqueous solutions in the presence of a double hydrophilic block copolymer poly(p‐hydroxystyrene‐b‐methacrylic acid), PHOS‐b‐PMAA, have been investigated. The studies aim to highlight both the possibilities and the limitations of CaCO3/PHOS‐b‐PMAA microparticle formation under different relative inorganic/polymer ratio conditions, varying the initial solution supersaturation or the polymer concentration. Scanning electron microscopy and atomic force microscopy were used to provide high‐resolution images of particles and thereby information on the particle morphology, while X‐ray diffraction analysis was used to determine the polymorph type and crystallite characteristics. The presence of the polymer in the composite particles was shown by thermogravimetric, particle charge density and zeta potential analysis. The polymer‐induced sensitivity of the new composites to environmental pH variations has been followed by streaming potential variation.